The effectiveness of a teaching -learning program according to the seven-cognitive model in the mathematical literacy among the fifth grade preparatory students - Khudhair, Laila Khalid; Jasim, A.S.D. Basim Mahammad (The journal of contemporary issues in business and government, 2021)
The aim of the current research is to identify the effectiveness of an educational program _Learn according to the cognitive model in the mathematical culture of the scientific fifth- grade students, as the research was limited to students of the fifth grade of the applied branch for the academic year 2020-2021, and the research sample consisted of (21) students for the experimental group, and ( 21) A student for the control group, and parity between the two groups was conducted in a number of variables, the researcher taught the experimental group according to the educational _ learning program, and the control group is taught in the usual way, and for the purpose of measuring the effectiveness of the educational program on the mathematical culture, the mathematical culture scale was built and consists of ( 40) A paragraph in four areas, and the results showed a clear effect of the educational program - the learning on the mathematical culture of the experimental group students who were taught according to the program.